Analysis of Madidihang Fish Handling at Ternate Archipelago Fishing Port, North Maluku Province - Tangke, Umar (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This research was conducted at the Ternate Nusantara Fishing Port (PPN), North Maluku Province in April 2023 with the aim of identifying the handling applied to madidihang fishing vessels in Ternate PPN, determining the effect of handling on the quality of madidihang landed at Ternate PPN and determining the appropriate form of handling on madidihang fishing vessels in Ternate PPN. This research uses a case study method conducted at Ternate VAT, a case study is a detailed examination of an object by focusing on a case intensively and in detail. In this case observing the effect of madidihang handling carried out while at sea and when unloading is carried out on the quality of madidihang with observations made on two ships namely: hand line ships and long boats. The results showed that the handling applied by hand line boats was better, based on the appearance of the landed madidihang, more brilliant and lack of scratches on the body and the proportion of defects (based on the weight of madidihang less than 17 kg) was smaller (5%) than the tonda fishing boat, the appearance was less brilliant and there were many scratches on the body of the landed madidihang and the proportion of defects was greater (based on the weight of madidihang less than 17 kg), by 27%.